2015 IEEE International Conference on Communication Workshop (ICCW) 2015
DOI: 10.1109/iccw.2015.7247358
|View full text |Cite
|
Sign up to set email alerts
|

One-bit massive MIMO: Channel estimation and high-order modulations

Abstract: Abstract-We investigate the information-theoretic throughout achievable on a fading communication link when the receiver is equipped with one-bit analog-to-digital converters (ADCs). The analysis is conducted for the setting where neither the transmitter nor the receiver have a priori information on the realization of the fading channels. This means that channel-state information needs to be acquired at the receiver on the basis of the one-bit quantized channel outputs. We show that least-squares (LS) channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 30 publications
3
139
0
Order By: Relevance
“…In summary, the results in [4], [7], [8], [11] suggest that massive MU-MIMO provides resilience against noise caused by coarse quantization. However, all these results pertain to massive MU-MIMO systems operating over frequency-flat fading channels.…”
Section: B Relevant Prior Artmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, the results in [4], [7], [8], [11] suggest that massive MU-MIMO provides resilience against noise caused by coarse quantization. However, all these results pertain to massive MU-MIMO systems operating over frequency-flat fading channels.…”
Section: B Relevant Prior Artmentioning
confidence: 99%
“…The analysis in [7] has been extended recently to higher-order modulation schemes in [8]. There, it was shown that amplitude information about the transmitted signal can be recovered even in the presence of a single-bit quantizer, provided that the number of receive antennas is sufficiently large and the signalto-noise ratio (SNR) is not too high.…”
Section: B Relevant Prior Artmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of such radically coarse quantization has been suggested for use in massive Multiple-Input Multiple-Output (MIMO) base stations, where the large number of radio chains makes high resolution quantization very power consuming [2]. Recent studies have shown that the performance loss due to the coarse quantization of one-bit ADCs becomes less severe as the number of receiving antennas grows; and, in a massive MIMO base station that has hundreds of antennas, the power saving that comes with one-bit ADCs might well outweigh this performance loss [3][4][5].…”
Section: Introductionmentioning
confidence: 99%